(untitled) (GYMNASIUM, 2017)
The aim of the study was the optimization of pirouettes execution technique of the young gymnasts, aged 7-9 years, by developing and implementing training programs including operational structures focused on dynamic and static balance. The research was conducted on a sample of work consists of 28 gymnasts aged 7-9 years, divided into two groups: experimental group (14) and the control one (14). The pedagogical experiment was conducted in training lessons during an annual cycle of unicycle type. Both groups of subjects performed a five training lessons per week of 90 minutes each. The comparison of the results obtained at the end of the experiment, between the experimental group and the control one shows significant differences from a statistical point of view, for all the evaluation tests underwent which confirms the hypothesis issued. Rationalization and operational structures algorithmization applied programs have proved effective indices shown by increasing the technical execution of pirouettes.